2021
DOI: 10.1007/s00204-021-03198-7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of breast cancer risk factors on proliferation and DNA damage in human breast glandular tissues: role of intracellular estrogen levels, oxidative stress and estrogen biotransformation

Abstract: Breast cancer etiology is associated with both proliferation and DNA damage induced by estrogens. Breast cancer risk factors (BCRF) such as body mass index (BMI), smoking, and intake of estrogen-active drugs were recently shown to influence intratissue estrogen levels. Thus, the aim of the present study was to investigate the influence of BCRF on estrogen-induced proliferation and DNA damage in 41 well-characterized breast glandular tissues derived from women without breast cancer. Influence of intramammary es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The research presented in this article aimed to identify and report the potential antidiabetic effects of specie B. aurea by reducing insulin resistance in animals with the disease. Previous studies reported the anti-inflammatory ( 14 , 17 ) and anticholinergic activities ( 18 ) of this plant. However, no studies are available on its antidiabetic activity.…”
Section: Introductionmentioning
confidence: 83%
“…The research presented in this article aimed to identify and report the potential antidiabetic effects of specie B. aurea by reducing insulin resistance in animals with the disease. Previous studies reported the anti-inflammatory ( 14 , 17 ) and anticholinergic activities ( 18 ) of this plant. However, no studies are available on its antidiabetic activity.…”
Section: Introductionmentioning
confidence: 83%
“…Recently, another research showed BMI is the only breast cancer risk factor that affect metabolic uxes to adducts of estrogens with DNA (via congruent adverse in uence on levels of estrogens, CYP1B1 and SULT1A2) [23]. These results suggest that SULT1A2 may be involved in the regulation of body weight and energy balance by regulating steroid metabolism [24].…”
Section: Discussionmentioning
confidence: 97%